Self-assembled pearl-necklace patterned upconverting nanocrystals with highly efficient blue and ultraviolet emission: Femtosecond laser based upconversion properties - Modak M.D.; Damarla G.; Maity S.; Chaudhary A.K.; Paik P. (My University, 2025)
This work reports new findings on the formation of a pearl-necklace pattern in self-assembled upconverting nanocrystals (UCN-PNs) which exhibit strong upconversion emission under an NIR excitation source of a femtosecond laser (Fs-laser). Each nano-necklace consists of several upconversion nanoparticles (UCNPs) having a size ca. 10 ± 1 nm. UCN-PNs are arranged in a self-organized manner to form necklace type chains with an average length of 140 nm of a single row of nanoparticles. Furthermore, UCN-PNs are comprised of UCNPs with an average interparticle separation of ca. 4 nm in each of the nanonecklace chains. Interestingly, these UCN-PNs exhibit high energy upconversion especially in the UV region on interaction with a 140 Fs-laser pulse duration at 80 MHz repetition rate and intense blue emission at 450 nm on interaction with a 900 nm excitation source is obtained. The preparation of self-assembled UCNPs is easy and they are very stable for a longer period of time. The emission (fluorescence/luminescence) intensity is very high which can make them unique in innumerable industrial and bio-applications such as for disease diagnosis and therapeutic applications by targeting the infected cells with enhanced efficiency. This journal is © The Royal Society of Chemistry.